Insular primary glioblastomas with IDH mutations: Clinical and biological specificities. Issue 3 (24th January 2017) - Hata, Nobuhiro; Hatae, Ryusuke; Yoshimoto, Koji; Murata, Hideki; Kuga, Daisuke; Akagi, Yojiro; Sangatsuda, Yuhei; Suzuki, Satoshi O.; Iwaki, Toru; Mizoguchi, Masahiro; Iihara, Koji
Abstract : Isocitrate dehydrogenase ( IDH ) mutation is a good prognostic marker for glioblastoma (GBM). Although it is infrequent in primary tumors, it is found in most lower‐grade gliomas. Thus, it is unclear whether IDH mutation is a marker for a specific phenotype of apparently primary de novo GBMs (pGBMs), or a marker for secondary tumors (sGBMs). We addressed this issue by analyzing clinical, radiographic and molecular findings in our institutional case series. Our cases included 92 pGBMs, with five cases of IDH1 mutations at R132 and no IDH2 mutations. The median overall survival of these five patients was 29 months (range: 4 to >40 months), which is considered good prognoses. Clinical and radiographic characteristics were distinct from IDH ‐wildtype ( IDH ‐wt) pGBMs. IDH ‐mutant ( IDH ‐mut) tumors consistently involved insular lesions and were subdivided into: (i) the two cases of elderly patients with long clinical histories and features implying multistep tumor development; and (ii) the three cases of younger patients with diffusely swelling insular tumors, slight contrast enhancement and no necrosis. Genetic and expression analyses of IDH ‐mut pGBMs were similar to those of sGBMs, suggesting that they are indeed distinct from their IDH ‐wt counterparts. TERT promoter mutation, a genetic marker of oligodendroglial derivation, was detected in one long‐surviving case, but genetic alterations in the astrocyte‐sGBM pathway were generally prevalent in IDH ‐mut pGBMs. Our results present a unique phenotype of IDH ‐mut pGBMs arising from insular cortex region, the molecular backgrounds of which are similar to sGBMs.